Patient portals and broadband internet inequality. (23rd March 2017) - Perzynski, Adam T; Roach, Mary Joan; Shick, Sarah; Callahan, Bill; Gunzler, Douglas; Cebul, Randall; Kaelber, David C; Huml, Anne; Thornton, John Daryl; Einstadter, Douglas
Abstract: Background: Patient portals have shown potential for increasing health care quality and efficiency. Internet access and other factors influencing patient portal use could worsen health disparities. Methods: Observational study of adults with 1 or more visits to the outpatient clinics of an urban public health care system from 2012 to 2015. We used mixed effects logistic regression to evaluate the association between broadband internet access and (1) patient portal initiation (whether a patient logged in at least 1 time) and (2) messaging, controlling for demographic and neighborhood characteristics. Results: There were 243 248 adults with 1 or more visits during 2012–2015 and 70 835 (29.1%) initiated portal use. Portal initiation was 34.1% for whites, 23.4% for blacks, and 23.8% for Hispanics, and was lower for Medicaid (26.5%), Medicare (23.4%), and uninsured patients (17.4%) than commercially insured patients (39.3%). In multivariate analysis, both initiation of portal use (odds ratio [OR] = 1.24 per quintile, 95% confidence interval [CI], 1.23–1.24, P  < .0001) and sending messages to providers (OR = 1.15, 95%CI, 1.09–1.14, P  < .0001) were associated with neighborhood broadband internet access. Conclusions: The majority of adults with outpatient visits to a large urban health care system did not use the patient portal, and initiation of use was lower for racial and ethnic minorities, persons of lower socioeconomic status, and those without neighborhood broadband internet access. These results suggest the emergence of a digital divide in patient portal use. Given the scale of investment in patient portals and other internet-dependent health information technologies, efforts are urgently needed to address this growing inequality.